Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

h (t) = 2t - 2 g(t) = 4t + 5 Find (h(g(t))

Sagot :

ANSWER:

[tex]h(g(t))=8t-8[/tex]

STEP-BY-STEP EXPLANATION:

We have the following functions:

[tex]\begin{gathered} h(t)=2t-2 \\ g(t)=4t+5 \end{gathered}[/tex]

To calculate h (g (t)) we must do the following:

[tex]\begin{gathered} h\mleft(g\mleft(t\mright)\mright)=2\cdot(4t+5)-2 \\ h(g(t))=8t+10-2 \\ h(g(t))=8t-8 \end{gathered}[/tex]